2020
DOI: 10.1109/tvcg.2020.2970525
|View full text |Cite
|
Sign up to set email alerts
|

A User-Centered Design Study in Scientific Visualization Targeting Domain Experts

Abstract: The development and design of visualization solutions that are truly usable is essential for ensuring both their adoption and effectiveness. User-centered design principles, which focus on involving users throughout the entire development process, are well suited for visualization and have been shown to be effective in numerous information visualization endeavors. In this paper, we report a two year long collaboration with combustion scientists that, by applying these design principles, generated multiple resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, the qualified scientists we have worked with are co-authors and helped design the system around their interests, so there is a level of potential bias that may be expected in their direct feedback, and the potential use cases for the methodology spans domains we are not experts in. Our vision for the future evaluation and refinement of the system involves iterative refinement based on lessons learned as we apply it in our domain [53], as well as through as much feedback as can be gained by other users outside our domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the qualified scientists we have worked with are co-authors and helped design the system around their interests, so there is a level of potential bias that may be expected in their direct feedback, and the potential use cases for the methodology spans domains we are not experts in. Our vision for the future evaluation and refinement of the system involves iterative refinement based on lessons learned as we apply it in our domain [53], as well as through as much feedback as can be gained by other users outside our domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also a few research studies that have comprehensively presented the formative evaluation process when designing a new search interface. Among the empirical studies appearing in this review book, Schlötterer et al (2020), Ye et al (2020) and Druin (2005) are selective studies that perform formative evaluations during the design process.…”
Section: Formative Evaluation and Summative Evaluationmentioning
confidence: 99%
“…In a long-term usage study, uptake of the visualization was observed, indicating that users deemed this new visualization system beneficial for their search interactions. Ye et al (2020) reported on a two-year project in which they applied design principles to develop effective and usable visualization solutions for combustion scientists. Their process consisted of three stages: the user and task analysis stage, the iterative design stage, and lastly the full realization stage.…”
Section: Formative Evaluation and Summative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation